Analysis of Students' Predicting Skills in The Concept of Reaction Rate - Nurul Salima; Hairida Hairida; Ira Lestari; Lukman Hadi; Masriani Masriani; Maria Ulfah (Universitas Pendidikan Mandalika, 2023)
The present research aimed to describe the skills of 11th grade students in predicting reaction rate material. The need for this study arose due to the inadequacy of the teacher's assessments to elaborate on the students' predictive skills, particularly in reaction rate material. The participants were 26 students from the 11th grade Science-2 class of State Senior High School (SMAN) 5 Pontianak. A quantitative description with a case study approach was used to gather data. The students were administered a questionnaire immediately after the reaction rate lesson, consisting of three questions. The mean scores of the students were analyzed to determine the results. The results showed that 50% of the students were categorized as having a very low level of skill in predicting reaction rate material, 27% as having a low level, 19% as having a medium level, 4% as having a high level, and 0% as having a very high level. It can be concluded that the majority of the students have a very low level of skill in predicting reaction rate material. The findings of this study have implications for teachers in creating more suitable lesson plans, syllabi, and media to align with the students' standard of competency outlined in the curriculum. This study may also serve as a foundation for future research on knowledge and education sustainability.